Perubahan Kenampakan Fisik Perkotaan Akibat Penerapan Permendikbud 51/ 2018 tentang Penerimaan Peserta Didik Baru Studi Kasus: Denpasar Utara-Bali - Parthami Lestari, Ayu Putu Utari; Primadewi, Siluh Putu Natha (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2020)
Urban as a macro architecture that is formed not only physically, but also socially, culturally, even politically, is always interesting to be observed. The 2019/2020 school academics year, for example, is the first time for new student enrolment which is based on their zoning residence. Permendikbud 51/2018 then regulates the discussion of student admission in public schoolssuch as atJunior, Middle and Senior. It is been recognized that urban traffic at the time of entry and return from school is one of the urban load, so schools often become the source of traffic. Due to the implementation of this regulation, students have to attend to school whereas neartheirhome is. It is then hoped that cities congestion will be reduced because students are no longer need to ride their vehicles to school. The research location will be focused on North Denpasar as the area with the largest number of public schools in Denpasar. The research method used is field observation, distributing questionnaires, interviews and literature studies. From the research results, it is concluded that in areas with high land use density, congestion still occurs due to school traffic. Meanwhile, in areas with low density, the phenomenon of land use to settlements has emerged.